Philippine financial almanac - Litiatco, Vicki J. (Manila Venture Unlimited, 1997)
A biannual publication alternating with the Philippine Banking Almanac. It includes different sectors in the Philippine financial system that play a crucial role in the economic development of our nation. It also contains a compendium of interesting and informative articles on the various sectors contained in the publication, and vital information on the individual companies comprising each sector.
The book comprises of two parts: the first is a compendium of interesting and informative articles on the different sectors the publication contains. Contributors are key government officials such as the Secretary of Finance, Governor of the Bangko Sentral ng Pilipinas, Chairman of Securities and Exchange Commission and presidents of associations and ranking officials of leading corporations of each sector. "The second part contains vital information on the individual companies comprising each sector. These were gathered either directly from the institutions or from the SEC, Insurance Commission, Bangko Sentral ng Pilipinas and their respective umbrella organizations/associations." (Preface) The listings include companies organized and registered during the first quarter of 1997. It is the aim of the publishers to present comprehensive and authoritative information but the vast number of entities involved makes it virtually impossible. Nonetheless, this publication offers substantial information to meet the urgent need of the different sectors of the business community. The latter part of the book presents data on the major associations (such as directors, officers, respective representatives and members) representing each sector. Certain government regulations which are vital to companies' decision making are included as well.
A biannual publication alternately with the Philippine Banking Almanac.
Keywords: Financial institutions -- Philippines -- Handbooks, manuals, etc; Banks and banking -- Philippines -- Handbooks, manuals, etc